Harmonization of Customs in the Practice of Friday Prayer Legality in Gorontalo City - Asaad, Misbahuddin; Husain, Muhammad Zakir (Jurnal Adabiyah, 2024)
This research aims to explore whether Friday prayers in Gorontalo City are conducted in harmony with both custom and religion. The essence of this implementation lies in how the sources of arguments are interpreted and their application understood, based on the theories and approaches employed. This research adopts a qualitative methodology with an analytical descriptive approach, phenomenological in nature, utilizing data from document studies, observations, and field interviews. The findings reveal that the roles, responsibilities, and tasks assigned to religious leaders and customary institution leaders in carrying out religious and customary processions consistently align with the legitimacy of both religion and custom. The primary goal of customary ceremonial activities is to fulfill religious purposes. The major events of the Friday festivities include sermons and prayers, organized in a specific manner: government officials are seated in the first row to the right of the pulpit, traditional authorities—comprising Bate (the traditional leader) and Wu’u (his deputy)—occupy the second row, while imams and syarak or syara dha’a employees are placed in the first row to the left. Customary institutions are further represented through parades led by government officials, religious authorities, and customary leaders. Ultimately, the purpose of Friday prayers and shaf (row) formations is to foster a solemn atmosphere of unity, enshrouded in ceremonial rhythms of worship. This atmosphere is considered conducive to receiving blessings and attaining merciful salvation. The "stick of trust" represents both symbolic and practical significance, offering spiritual rewards. During the Friday prayer procession, its utility extends beyond mere symbolism. الملخص يهدف هذا البحث إلى استكشاف ما إذا كانت صلاة الجمعة في مدينة غورونتالو تُنفذ بطريقة تتوافق مع العرف والدين. أما الشكل الحقيقي لهذا التطبيق فيتمثل في طريقة تفسير مصدر الحجة فهم تطبيقها بناء على النظريات والمناهج المستخدمة. هذا البحث عبارة عن دراسة نوعية ذات منهج تحليلي وصفي تحليلي ذو طبيعة ظواهرية باستخدام بيانات من دراسات وثائقية وملاحظات ومقابلات ميدانية. وجدت أن الأدوار والمسؤوليات والمهام الموكلة للزعماء الدينيين وقادة المؤسسات العرفية في تنفيذ المواكب الدينية والعرفية ترتبط دائمًا بشرعية الدين والمؤسسات العرفية. إن تحقيق الأهداف الدينية هو الغرض الرئيسي من الأنشطة الاحتفالية التقليدية. والفعاليات الرئيسية في احتفالات الجمعة هي الخطب والصلوات. ويتم تنظيم ذلك بطريقة معينة: حيث يتم تعيين المسؤولين الحكوميين في الصف الأول على يمين المنبر، ويحتل جهاز العاديات - الذي يتألف من الباتي، زعيم العاديات، ونائبه، الصف الثاني من الصفوف، ويتم تعيين الأئمة ومسؤولي السرك أو الشرع دأ في الصف الأول من الصفوف على اليسار. ويتم تمثيل المؤسسات العرفية من خلال مسيرات يقودها المسؤولون الحكوميون والزعماء الدينيون والزعماء التقليديون. وفي نهاية المطاف، فإن الغرض من صلاة الجمعة وتشكيل الصفوف هو خلق جو من الوحدة المهيبة والوقار تغلفه إيقاعات العبادة الاحتفالية. هذا الجو يساعد على تلقي البركة ونيل البركة. إن هذا العود الثقة هو الذي يقدم الفضل. خلال موكب صلاة الجمعة، فإن عصا الإيمان هي أداة للتشريف في موكب صلاة الجمعة وليست مجرد أداة رمزية. Abstrak Penelitian ini bertujuan untuk mengeksplorasi apakah salat Jumat di kota Gorontalo dilaksanakan dengan cara yang selaras dengan adat dan agama. Wujud nyata pelaksanaan ini terletak pada cara interpretasi sumber dalil dan pemahaman aplikasiannya berdasarkan teori dan pendekatan yang dipergunakan. Penelitian ini merupakan kajian kualitatif dengan pendekatan deskriptif analitis yang bersifat fenomenologi dengan menggunakan data hasil studi dokumen, pengamatan, serta wawancara lapangan. Penelitian ini menemukan bahwa peran, tanggung jawab, dan tugas yang diberikan kepada para pemuka agama dan tokoh-tokoh lembaga adat dalam melaksanakan prosesi keagamaan dan adat selalu berkorelasi dengan legitimasi agama dan lembaga adat. Pencapaian tujuan keagamaan adalah tujuan utama dari kegiatan upacara adat. Acara utama dalam perayaan hari Jumat adalah khotbah dan doa. Kegiatan ini diatur dengan cara tertentu: pejabat pemerintah ditugaskan di barisan pertama di sebelah kanan mimbar, aparat adat yang terdiri dari Bate, pemimpin adat, dan Wu’u, wakilnya menempati barisan shaf kedua, dan para imam dan pegawai syarak atau syara’ dha’a ditugaskan di barisan shaf pertama di sebelah kiri mimbar. Lembaga-lembaga adat ditunjukkan melalui pawai yang dipimpin oleh pejabat pemerintah, pemuka agama, dan pemuka adat. Pada akhirnya, tujuan dari salat Jumat dan pengaturan shaf adalah untuk menciptakan suasana persatuan yang khusyuk dan khidmat yang diselimuti oleh ritme ibadah seremonial. Suasana ini kondusif untuk menerima berkah dan meraih rahmat. Dan tongkat kepercayaan yang dipegang khatib inilah yang menawarkan pahala. Selama prosesi salat Jumat, tongkat ini memiliki lebih banyak kegunaan daripada sekadar makna simbolis.